2020
DOI: 10.1021/acs.est.0c01832
|View full text |Cite
|
Sign up to set email alerts
|

HONO Budget and Its Role in Nitrate Formation in the Rural North China Plain

Abstract: Nitrous acid (HONO) is a major precursor of tropospheric hydroxyl radical (OH) that accelerates the formation of secondary pollutants. The HONO sources, however, are not well understood, especially in polluted areas. Based on a comprehensive winter field campaign conducted at a rural site of the North China Plain, a box model (MCM v3.3.1) was used to simulate the daytime HONO budget and nitrate formation. We found that HONO photolysis acted as the dominant source for primary OH with a contribution of more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(142 citation statements)
references
References 63 publications
20
122
0
Order By: Relevance
“…It proves the similar source of PAN and HCHO, also demonstrates a potential impact of HCHO photolysis on PAN increase at this rural site with accelerated photochemistry. The sources of HOx radical during cold days have been a subject of recent interest in the field of atmospheric chemistry over the NCP region (Tan et al, 2018;Xue et al, 2020), and most of them reported the importance of HONO in OH radical and atmospheric oxidation capacity during cold days over the NCP. By comparisons, our results at the SDZ site presents a much lower HONO concentration (average: Tan et al (2018) and Xue et al (2020).…”
Section: Impacts Of Radicals On Rapid Increase Of Panmentioning
confidence: 99%
See 2 more Smart Citations
“…It proves the similar source of PAN and HCHO, also demonstrates a potential impact of HCHO photolysis on PAN increase at this rural site with accelerated photochemistry. The sources of HOx radical during cold days have been a subject of recent interest in the field of atmospheric chemistry over the NCP region (Tan et al, 2018;Xue et al, 2020), and most of them reported the importance of HONO in OH radical and atmospheric oxidation capacity during cold days over the NCP. By comparisons, our results at the SDZ site presents a much lower HONO concentration (average: Tan et al (2018) and Xue et al (2020).…”
Section: Impacts Of Radicals On Rapid Increase Of Panmentioning
confidence: 99%
“…The sources of HOx radical during cold days have been a subject of recent interest in the field of atmospheric chemistry over the NCP region (Tan et al, 2018;Xue et al, 2020), and most of them reported the importance of HONO in OH radical and atmospheric oxidation capacity during cold days over the NCP. By comparisons, our results at the SDZ site presents a much lower HONO concentration (average: Tan et al (2018) and Xue et al (2020). As the SDZ site is located in the north border of the NCP region, which is much cleaner than the suburban and rural site in Tan et al (2018) and Xue et al (2020), then less affected by shortlive species, such as NOx and HONO.…”
Section: Impacts Of Radicals On Rapid Increase Of Panmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, HONO photolysis can dominate OH production during the morning hours in some environments (Volkamer et al, 2010), but decrease in importance during the day as the concentration of HONO decreases. 40 However, in several instances HONO photolysis has been shown to be a significant OH source through the day (Kleffmann et al, 2005;Acker et al, 2006;Ren et al, 2013;Griffith et al, 2016;Xue et al, 2020). This is mainly due to higher-than-expected daytime HONO mixing ratios that cannot be attributed to gas-phase reactions (R1-R3) (Tang et al, 2015;Lee et al, 2016;Meusel et al, 2016;Xue et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other HONO sources include direct emission from vehicles or other combustion sources (Kirchstetter et al, 1996;Kurtenbach 45 et al, 2001;Li et al, 2008;Xu et al, 2015), direct photolysis of some species (Bejan et al, 2006;Zhou et al, 2011), photo-enhanced surface reactions (George et al, 2005;Stemmler et al, 2006), and release from soil due to biological processes (Su et al, 2011;Oswald et al, 2013;Weber et al, 2015;Meusel et al, 2018). Lastly, several production pathways involving the heterogeneous conversion of NO2 to HONO on soil, leaf canopies, aerosols, and other surfaces have been suggested to explain higher-than-expected HONO mixing ratios observed during some field campaigns (Kleffmann et al, 1998;Ramazan et al, 2004;Stutz et al, 2004;Xue et al, 2020). 50 HONO is also an important pollutant within the indoor environment.…”
Section: Introductionmentioning
confidence: 99%